2020
DOI: 10.3233/jsa-200436
|View full text |Cite
|
Sign up to set email alerts
|

Naive Bayes approach to predict the winner of an ODI cricket game

Abstract: This paper presents findings of a study to predict the winners of an One Day International (ODI) cricket game, after the completion of the first inning of the game. We use Naive Bayes (NB) approach to make this prediction using the data collected with 15 features, comprised of variables related to batting, bowling, team composition, and other. Upon the construction of an initial model, our objective is to improve the accuracy of predicting the winner using some feature selection algorithms, namely univariate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…11,12 In literature related to cricket, it can be observed that different feature selection methods have been tried and tested with a variety of approaches. Prominently, Wickramasinghe 8 emphasizes the impact of using different feature selection methods in cricket by comparing the results of univariate, recursive elimination, and principal component analysis. Based on the results, Wickramasinghe claims that the prediction accuracy reaches the highest when using the univariate feature selection method.…”
Section: Feature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In literature related to cricket, it can be observed that different feature selection methods have been tried and tested with a variety of approaches. Prominently, Wickramasinghe 8 emphasizes the impact of using different feature selection methods in cricket by comparing the results of univariate, recursive elimination, and principal component analysis. Based on the results, Wickramasinghe claims that the prediction accuracy reaches the highest when using the univariate feature selection method.…”
Section: Feature Analysismentioning
confidence: 99%
“…The results of the study indicate that they have achieved accuracy levels ranging from 65.79% (first over) to 84.15% (19 normalth over) across the second innings. By focusing on ODI cricket, Wickramasinghe 8 presents an in-game predictor with a Naive Bayes based approach where the study predicts the winner after the end of the first innings of the match. In his research study, he has achieved a maximum accuracy of 85.71% while investigating how different combinations of training/testing sample sizes and feature selection methods affect the results.…”
Section: Introductionmentioning
confidence: 99%
“…Cricket is a top-rated game. Cricket is reasonably significant within the statistical science community, but this game's unpredictable and unstable nature makes it more challenging to use in standard probability models [1,4,5]. Uncertainty is the feature of cricket, and it increases as the game becomes shorter.…”
Section: Introductionmentioning
confidence: 99%
“…With millions watching cricket, building a model for forecasting the outcome of cricket matches is a real-world task. Sports Analytics is used to determine a cricket match outcome, whether the game is in progress or well before the game begins [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques based on computer vision for Physical Activity Recognition (PAR) have mainly used [36]: red-green-blue (RGB) images, optical flow, 2D depth maps, and 3D skeletons. They use diverse algorithms, such as Naive Bayes (NB) [37], Decision Trees (DT) [38], Support Vector Machines (SVM) [39], Nearest Neighbor (NN) [40], Hidden Markov Models (HMM) [41], and Convolutional Neural Networks (CNN) [42].…”
Section: Introductionmentioning
confidence: 99%